Effect of fuel type on the optimum thickness of selected insulation materials for the four different climatic regions of Turkey - Ucar, Aynur; Balo, Figen (Elsevier Sci Ltd, 2009)
The optimum insulation thickness of the external wall for four various cities from four climate zones of Turkey, energy savings over a lifetime of 10 years and payback periods are calculated for the five different energy types and four different insulation materials. Foamboard 3500, Foamboard 1500, extruded polystyrene and fiberglass as insulation material are selected. In this study, it is calculated the value of the amount of the net energy savings using the P-1-P-2 method. The results show that optimum insulation thicknesses vary between 1.06 and 7.64 cm, energy savings vary between 19$/m(2) and 47 $/m(2), and payback periods vary between 1.8 and 3.7 years depending on the city and the type of fuel. The highest value of energy savings is reached in Agri for LPG fuel type, while the lowest value is obtained in Aydin for natural gas. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Optimum insulation thickness; Energy savings; Life-cycle cost